Agriculture, diffusion, and development: Ripple effects of the neolithic revolution - Louis Putterman (Brown University, Department of Economics, 2006)
Are the Neolithic revolution's effects still impacting incomes across the world today? I find strong support for this proposition using new, country-specific estimates of the timing of agricultural transition. While support with my data is slightly weaker than with the coarser data of Hibbs and Olsson (2004), I provide evidence that the differences are due to how technological diffusion is accounted for. A correction for world migrations since 1500 significantly improves the fit. Transition year also helps to explain income in 1500 itself, and an alternative measure of pre-modern development, state history, has similar ability to predict income in 1500 and 1997.
Keywords: N50; O10; O40; Q10; 330; economic growth; agriculture; transition to agriculture; Neolithic Revolution; Agrargeschichte; Vorgeschichte